PENERAPAN ICE BREAKING (PENYEGAR PEMBELAJARAN) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VIII A MTs AN-NUR PELOPOR BANDARJAYA TAHUN PELAJARAN 2013/2014 - Kurniasih, Ayu Novia; Alarifin, Dedy Hidayatullah (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The purpose of this research is to know the result of learning in IPA by using ice breaking of the student of the eighth grade class of in MTs An-Nur Pelopor Bandarjaya TP. 2013/2014. The subjeck of this research is class Â MTs An-Nur Pelopor Bandarjaya the sums of the students are 31. This research is CAR (Classroom Action Research) that is consists of 2 cycles,one cycle consist of three meeting included of test. The test is conducted in every last meeting. The result of learning could see of the test that is given by the teacher, the implementation of learning process by using ice breaking by using observing that is written by observer. From the result of research got the result of studentâs learning is 58,06% in the first cycle, and 77,42% in the second cycle. From the minimum requirement (KKM) namelyÂ . The average of the result of the studentâs learning is 66,29 in the frist cycle and 72,09 in the second cycle. So, it can be inferred that by using ice breaking can increase the result of studentâs learning.